Secondary school teachers' participation in school's decision making / Siti Nursheila Khairuddin - Khairuddin, Siti Nursheila (2012)
This study was about secondary school teachers' participation in school's decision-making in Kuching Division. The purpose of this study is to identify the level of secondary school teachers' actual and desired participation in school's decision-making. Besides that, it is also to examine the patterns of actual and desired participation exist for secondary school teachers according to their years of working experience, gender and position in school. There were five categories of decisional situations namely curriculum and instruction, student-related issues, managing colleagues, school policy and school fond. This research was conducted using a survey method. The questionnaire was used to obtain responses from 120 teachers from four schools selected in Kuching Division. The data was analyzed using statistical package, the SPSS version 16.0 and responses were reported by frequency, percentage, mean and standard deviation. The results of the study revealed that the secondary school teachers did not show high level of participation in school's decision-making. The secondary school teachers' desired participation was found higher which exceeded their level of actual participation in the five categories of decisional situations. Besides that, results also showed that teachers with more than 10 years have the highest actual participation in most of the 25 decisional situations. Female teachers were more likely to be involved in the classroom management issues while male teachers showed interest to participate in deciding the managerial domain. Based on the findings in the study, secondary school teachers have shown their readiness to participate and involved in school's decision-making. Some recommendations for practice were put forward for consideration by the Ministry of Education.